Intelligence Investigation of the Crime of Online Gambling to Eliminate Gambling Practices at the Pemalang Police - Rahmat Hasan (Advances in Police Science Research Journal, 2022)
Intelligence investigation is one of the principal duties of members of the intelligence force in the law enforcement efforts of society. This research carried out because of the proliferation and increase in gambling and also gambling practices that have also improved, from manual gambling to online gambling in the affected district. This is due to the not yet optimal Intelligence Investigation of the Crime of Online Gambling to Eliminate Gambling Practices at the Pemalang Police. This research described the competence of members, the integrity of members, and the implementation of intelligence investigations by members of the intelligence units against the online criminal gambling in the affected areas. This research approach carried out by the writer involves a qualitative approach. The aim of this research is to get an idea of the real picture of the data source that researchers have obtained that is, the primary data source derived from interviews and secondary data sources is derived from document analysis. Some findings in this research, which is the lack of members' competence of information technology and the regulated legislation on gambling, members who tend to be lazy and undisciplined in addressing criminal gambling and members who lack the experience of carrying out intelligence investigations. The authors suggest a more sophisticated and advanced enhancement of tools and infrastructure, an increase in and implanting of integrity on personnel, and the courage of personnel to take police force into action. So it is hoped that the implementation of the intelligence investigation can run optimal.